Adolescents with chronic disease and social media: a cross-sectional study. Issue 8 (15th January 2020) - De Nardi, Laura; Trombetta, Andrea; Ghirardo, Sergio; Genovese, Maria Rita Lucia; Barbi, Egidio; Taucar, Valentina
Abstract : Objective: This study aims to explore the attitude of adolescents with chronic diseases toward social media exposure, focusing in particular on Facebook. Design: Cross-sectional study. Setting: An anonymous semistructured survey was distributed to an Italian hospital-based cohort of adolescents with chronic disease to explore the role of Facebook in their daily life. Patients: We recruited 212 adolescents (aged between 13 and 24 years) with a diagnosis of inflammatory bowel disease, coeliac disease, diabetes mellitus type 1 and cystic fibrosis. Results: Two hundred and seven of the 212 (97.6%) expressed the need of sharing their illness experience with friends, 201 out of 212 (94.8%) usually searched information on the internet to find new therapies and to discover their prognosis. One hundred and forty-nine out of 212 adolescents (70.3%) perceived dependence on their parents as the most negative aspect of having a chronic disease, and 200 out of 212 (94.3%) were looking for friends with the same disease on Facebook. Two hundred and ten out of 212 (99.1%) did not want their doctors or nurse on their social media platforms. During the active disease periods, the time spent with social media increased from an average of 5 to 11 hours. Conclusions: This descriptive analysis focused on the Facebook impact on chronic disease perception among affected adolescents. It showed that they used to spend an increased amount of time on this platform during disease flare-up and highlighted their wish of keeping doctors and nurses away from their social dimension.